Pembinaan Kesadaran Hukum bagi Anak dan Remaja - Mustafa Bola; Muhammad Ashri; Zulkifli Aspan; Muh. Ilham Arisaputra; Romi Librayanto; Eka Merdekawati Djafar; Dian Utami Mas Bakar (Faculty of Law Hang Tuah University, 2016)
The Act No. 23 of 2003 on Children Protection obligates the state and government to ensure children protection, maintenance, and welfare. A child who obtains criminal sentence has been protected by the government based on the Act No. 12 of 1995 on Children Immurement. The Act pays attention to their interests in order to not eliminate the child's future. The children criminal sanction is given as a process of building children awareness to understand the better future. A form of the government protection to children is legislation on children welfare, juvenile justice, human rights, children immurement, and children protection. The children and adolescents committing the criminal acts are very serious issues to immediately overcome by the concerned parties i.e. the parents, police, and teachers that have many direct contact with children and adolescents. The police are expected to take action against any perpetrators of crimes, including those committed by children and adolescents. Meanwhile, the parents and the teachers are expected to give serious guidance in order that they are able to be the pride of, not the ‘dregs of society’.